Improving The Knowledge of Health Cadre on The Early Detection of Cervic Cancer - Veronika Ofong; Chatarina Umbul Wahyuni; Supaat Supaat (Health Notions, 2018)
Background: One of the efforts to prevent cervical cancer is through The Visual Inspection with Acetic Acid (VIA) test the health cadre is an extension of health workers in conducting socialization regarding VIA test. The purpose of this study was to look at the differences in the knowledge of health cadres before and after being given training. Methods: The study conducted at 2018. The study design was a non randomized pre-test posttest design. The sample in the study were all cadres who followed the pretest and posttest as many as 35 respondents. The data were analyzed by using Wilcoxon test. Result: The results showed there were differences in knowledge before and after training (p=0.000). Conclusion: There is a significant difference in knowledge among health cadres at Taman Publich Health Center before and after get training. Keywords: Cervical cancer, VIA test, Cadre, Knowledge